Singularidades do trabalho gerencial da enfermeira no contexto do serviço de atendimento móvel de urgência de Minas Gerais - Elisangela Guimaraes Soares (2009)
SAMU 192 is a strategy of calling attention to the population health intending to decrease theimpacts of morbid mortality and the worsening to the health, attending to urgent andemergency situations, clinic or traumatic. The first units were set in 2004, initially covering27 cities. It is a new setting of production of health in which the building of the services andfunctions has happened in an empiric way. SAMU 192 has three coordinating groups toguarantee the process of being executed: a general section, the doctors section and the nursingsection, being the two last ones submitted to the first one, in an hierarchy way. The nursingdepartment corresponds to the larger contingent and its way of working is out of sight of thenursing management, unlike the reality presented in the hospital context. A straightparticipation of the nurse whos in charge of managing the group must be clear and effective,since the team works most of the time out of the manager view, becoming necessary to knowcarefully his/her way of developing the management job. Since then, this study was developedwith the objective to know singularities of the management job of the nurse who coordinatesthe nursing team at SAMU, because this is a new area in health field, being built at presenttimes. It was developed a study with a new qualitative approach, as a case study. The placesbeing studied were three units of SAMU-192 in Minas Gerais State: the cities of GovernadorValadares, Ipatinga and Itabira. Places where the nurse is the chief of the nursing team. Thestudies were done with nine people. The results were analyzed in their contents and discussedwith the researched literature. It was noticed characteristics that referred to the process ofworking of the manager nurse, his/her autonomy, tasks and personal relationships. Throughthe results, it was possible to observe that it was an organized group mainly because of theconstruction and keeping of the affection, psychological and ideological ties. The great reasonto accept a managing office is the possibility of overcoming a challenging job. And keeping itdepends on recognizing the manager nurse role, inter and extra institutions. Nevertheless, itwas reported several facilities and difficulties practicing this office. Confidence, good relationand the respect between manager and team are positive aspects as well as the managing oflack of resources, conflicts and bad professional training to the emergency cases are negativeones. The negative aspects are increased by the politic obstacles inherent in the publicservices. At last, it is observed that the manger nurse has improved a lot trying to build his/heridentity, being between the phases of identity and elaboration. The elaboration phase seems tobe closest to reality due to the modifications in the current outdate scenery and to the embryophase that it SAMU is inserted.